Post-field grinding evaluation of different rail grades in full-scale wheel/rail laboratory tests. (January 2023) - Mesaritis, M.; Santa, J.F.; Molina, L.F.; Palacio, M.; Toro, A.; Lewis, R.
Abstract: Rail grinding is a maintenance task performed in the field to return it to profile and/or remove damage, however, it can affect the surface integrity of the rail. In this paper, the damage resistance of three different ground rails (R260, R350HT and R400HT) was evaluated. Rail samples were ground using the same parameters in a low-traffic line in the field. The rail metallurgy was then examined, and white etching layer (WEL) formation was evaluated. The resistance to wear and rolling contact fatigue (RCF) was studied in a Full-Scale Rig (FSR). Cracking was detected and, in some cases, WEL was found pressed into the pearlitic microstructure whereas in others the bonding between the WEL and the pearlite failed leading to delamination. Highlights: Grinding was performed on three different rails in a low-traffic line in the field. Microstructural analysis performed on the field samples indicated the presence of WEL. Full-scale rolling/sliding experiments were performed to investigate the post-grinding performance. Results exhibited that WEL performance varied within the different rail grades. Debris and roughness values were collected throughout the rolling/sliding testing.